Model Pembelajaran Islam Berbasis Multimedia Interaktif untuk Anak Usia Dini di Era Digital - Syafitri, Dina (AUD Cendekia: Journal of Islamic Early Childhood Education, 2024)
This study aims to analyze and describe the model of Islamic learning based on interactive multimedia for early childhood at RA Muslimat Miga in the context of the digital era. This research employs a qualitative method with a phenomenological approach to gain an in-depth understanding of teachers’, children’s, and the school environment’s experiences in implementing interactive media in Islamic education. Data were collected through observation, in-depth interviews, and documentation involving six main informants consisting of the head of the RA, four teachers, and one parent. The results show that the use of interactive multimedia such as Islamic animation videos, educational applications, and audio-visual media effectively enhances learning motivation, deepens children’s understanding of Islamic values, and strengthens their religious character. Teachers play a crucial role as facilitators and media creators who adapt learning content to the developmental stages of early childhood. This model demonstrates a collaborative, enjoyable, and meaningful learning process without neglecting core Islamic spiritual values. Theoretically, this study enriches the body of knowledge on technology-based Islamic learning, while practically it provides an alternative model relevant for Islamic early childhood education institutions to face the challenges of educational modernization.